Upaya Penanganan Nutrisi Pada Pasien Dengan Hipertensi - Yullianti, Try Affita Ajeng, ArinaMaliya, S.Kep. Ns.,M.Si.Med, Ns. AriefWahyudiJadmiko, S.Kep.,M.Kep (2017)
The prevalence of hypertension continues to increase both in developed countries and in developing countries at this time. Hypertension is an increase in blood pressure which systolic pressure ≥ 140 mmHg, while diastolic blood pressure ≥ 90 mmHg. Factors causing hypertension is diet, age, gender, and ethnicity, as well as genetic factors and environmental factors such as alcohol, salt, smoking, obesity, and stress. The types of foods that cause hypertension are junk foods which contains preservatives, salt levels are too high, and excess consumption of fat. Blood pressure that gives symptoms is continuing cause more severe damage such as stroke, coronary heart disease, as well as a narrowing of the left ventricle / left ventricle of. Hypertension can also cause kidney failure, other blood diseases, and diabetes mellitus. Hypertension can cause structural and functional changes in peripheral blood vessels responsible for blood pressure. Such changes occur in atherosclerosis, loss of elasticity of the connective tissue that causes a decrease distention and blood vessel tense power. There are several ways to reduce blood pressure is one way to a low-salt diet. The low-salt diet is a diet by eating food without salt altogether and reducing the use of foods high in sodium content